NLRP3 Inflammasome Signaling as a Link Between HIV-1 Infection and Atherosclerotic Cardiovascular Disease - Mullis, Caroline; Swartz, Talia H. (Frontiers in Cardiovascular Medicine, 2020)
36.9 million people worldwide are living with HIV-1. The disease remains incurable and HIV-infected patients have increased risk of atherosclerosis. Inflammation is a key driver of atherosclerosis, but no targeted molecular therapies have been developed to reduce cardiovascular risk in people with HIV-1 (PWH). While the mechanism is unknown, there are several important inflammatory signaling events that are implicated in the development of chronic inflammation in PWH and in the inflammatory changes that lead to atherosclerosis. Here we describe the pro-inflammatory state of HIV-1 infection that leads to increased risk of cardiovascular disease, the role of the NLR Family Pyrin Domain Containing 3 (NLRP3) inflammasome in HIV-1 infection, the role of the NLRP3 inflammasome in cardiovascular disease (CVD), and outline a model whereby HIV-1 infection can lead to atherosclerotic disease through NLRP3 inflammasome activation. Our discussion highlights the literature supporting HIV-1 infection as a stimulator of the NLRP3 inflammasome as a driver of atherosclerosis.